Synthesis and Photoswitching Properties of Aznzene Liquid Crystals with a Pentafluorobenzene Terminal - Lutfor, M. R.; Hegde, Gurumurthy; Sarkar, Shaheen M.; M. M., Yusoff (Chinese Chemical Society, 2014)
The fluorine-substituted benzoate ester rod-shaped liquid crystals containing an azobenzene side chain linked with terminal double bonds were synthesized and characterized. The mesophase and photoswitching properties were determined by polarizing optical microscopy (POM), differential scanning calorimetry (DSC) and UV–visible spectrometry. The rod-shaped compound 4a having an odd number of carbon atoms in the alkyl chains exhibits nematic phase and SmA type phase whereas compound 4b having an even number of carbon atoms showed only nematic phase. Both fluorine containing compounds 4c and 4d showed only SmA type phases. The photoswitching properties of these compounds showed a rate of trans to cis isomerization ranging 19–20 s, whereas reverse process took around 230 min in solution. These materials may be ideal in the field of optically rewritable applications where both on and off rates should be crucial.